PENGETAHUAN PERPAJAKAN, SOSIALISASI PERPAJAKAN, DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK - Meiska Lianty; Dini Wahjoe Hapsari; Kurnia K (JRAK, 2017)
This study aims to discover how the effect of the tax knowledge, tax socialization, and tax authorities service, either simultaneously or partially, on the taxpayers compliance in KPP Pratama Bandung Bojonagara. The research samples are the whole number of the non-employee individual taxpayers in the amount of 100 people. The sampling technique is convenience sampling and the analysis method is using multiple linear regression. Simultaneously, the tax knowledge, the tax socialization, and the tax authorities service significantly affect the taxpayers compliance in KPP Pratama Bandung Bojonagara. Partially, the result shows that both the tax knowledge and the tax authorities service significantly have positive effect and are directly proportional on the taxpayers compliance. On the other hand, the tax socialization has no significant effect on the taxpayers compliance in KPP Pratama Bandung Bojonagara.